Peran Patroli Roda Dua Satuan Sabhara dalam Pencegahan Pencurian Kendaraan Bermotor - Wigrha Mustika Rahmah (Advances in Police Science Research Journal, 2019)
Motor vehicle theft is one of the major crimes in Tasikmalaya. Despite the fact that there are fluctuations in crime numbers every year, this crime always comes on top of the list. Motorcycle patrol functions as a preventive measure by the police department for motor vehicle theft. The purpose of this research is to analyze and describe factors and measures that affect Sabhara Unit’s motorcycle patrol. The location of this research is at Polres Tasikmalaya focusing on Sabhara Unit’s motorcycle patrol. This research uses qualitative methodology with technical descriptive analysis. The data are triangulated using two kinds of techniques which are technical sources and primary, secondary, and tertiary sources. Validity of data that are used are data reduction, data presentation, conclusion and verification. This research uses management theory, crime prevention theory, and the concept of patrol. The non optimality of motorcycle patrols conducted by the Turjawali task force is analyzed by its functionality. The motorcycle patrols are conducted on the same route with the car patrols, and the target areas are just around the central part of the city. There are some internal and external factors that caused this non optimality. The internal factors are the members, the budgets, tools and vehicles, and work delegation methods. The external factors are the citizens of Tasikmalaya and their economic situation. The conclusion of this research is that Turjawali task force’s motorcycle patrols are still not optimal, and the biggest factor contributed to this is the member’s competence